Development of the Learning Behavior During the Lesson "Circle" in Children with Severe Multiple Developmental Disorders - M.A. Vetrova; A.O. Vetrov; A.S. Migachev (Moscow State University of Psychology and Education, 2022)
We present the development of the learning behavior patterns in children with autism spectrum disorders (ASD) with severe multiple developmental disorders (SMDD) on the model of a number of individual behavioral patterns of which the group activity “Circle” consists. The “Circle” is one of the most important organizational activities in the classroom. The study involves a class consisting of five children with severe and multiple developmental disabilities (SMDD) enrolled in the special school education program for children with ASD (so-called adopted general education program type 8.4). Present article covers the issues of the structure of the stereotype of the learning behavior, the aims of the planning psycho-educational work. As a result of the training, all children showed positive dynamics. Also, concomitant positive changes were noted associated with adaptation to schooling. After additional evidence-based studies, it is possible to transfer the practice to work with children with other developmental disorders.